Analysis of the Relationship between Music and the Human Soul with Emphasis on Avicennism-Psychology - Muhammad Javad Pashaei (آموزه‌‌های فلسفه اسلامي, 2021)
Undoubtedly, the history of music should be compared with the history of human life; because for a long time, various types of music derived from the text of nature have been associated with human societies. Music in a general view can be divided into natural and artistic (artificial). Ibn Sina (Avicenna) was one of the greatest thinkers and philosophers who spoke about art music in detail in his writings and this has exposed his views to more criticism and comments. However, the capacities of Avicenna philosophy in expressing the effects of music on the state of the human soul have not been revealed much. The main question of this article is what the relationship between music and the human soul in terms of Avicennism-psychology is? In an analytical descriptive approach and emphasizing the principles of Avicennism-psychology, the author has come to the conclusion that artistic music, with its direct impact, targets only the vegetable and soul (sprit) in humans, and theoretical and practical reason (conceptual and practical intellect) also often indirectly exposes him to these disturbances with its excessiveness and deviant (exess and neglect) effects on these faculties.